2008
DOI: 10.1002/ptr.2435
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids, taxifolin and luteolin attenuate cellular melanogenesis despite increasing tyrosinase protein levels

Abstract: Flavonoids are a group of polyphenolic compounds widely distributed in plants. Their potent bio-activities and relatively low toxicity have rendered them useful ingredients in functional cosmetics. The purpose of the present study was to examine their potential effects on cellular melanogenesis. When tested in murine melanoma B16F10 cells activated by alpha-melanocyte stimulating hormone (alpha-MSH), taxifolin and luteolin inhibited the cellular melanogenesis as effectively as arbutin, one of the most widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 32 publications
2
77
0
Order By: Relevance
“…Studies have shown that EGCG, catechins, luteolin, baicalein and kaempferol are flavonoids with antioxidation activity. These compounds display antimelanoma effect via inhibiting cell proliferation, invasion and inducing apoptosis with multiple pharmacological mechanisms [25][26][27][28][29][30][31][32]. Flavonoids exhibit anti-proliferative and apoptotic effects via HGF/SF-Met signaling, PI3K-AKT pathway, MAPK pathway or cell cycle regulation in melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that EGCG, catechins, luteolin, baicalein and kaempferol are flavonoids with antioxidation activity. These compounds display antimelanoma effect via inhibiting cell proliferation, invasion and inducing apoptosis with multiple pharmacological mechanisms [25][26][27][28][29][30][31][32]. Flavonoids exhibit anti-proliferative and apoptotic effects via HGF/SF-Met signaling, PI3K-AKT pathway, MAPK pathway or cell cycle regulation in melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, luteolin (3', 4', 5, 7-tetrahydroxyflavone) is a well kwon flavonoid. Previous study has indicated that luteolin inhibited melanin synthesis in B16 melanoma cells [25]. 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH assay), ferric reducing antioxidant power (FRAP assay) and ABTS assay are in vitro antioxidation assays.…”
Section: Discussionmentioning
confidence: 99%
“…UPLC-HRMS also facilitated the identification of the two bioactive principles as luteolin and apigenin. If luteolin was already known as a skin-lightening agent [37], apigenin was only reported to be a weak tyrosinase inhibitor, an observation that might be biased by its low solubility in water-based medium [43,44]. Their whitening potencies were hence further confirmed by tyrosinase inhibitory assays that were performed on analytical standards in the same experimental conditions as the ones that were used to assess the activities of the R. luteola extracts and fractions: both luteolin and apigenin appear to be potent tyrosinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin's anti-allergic, anti-oxidant, anti-carcinogenic, anti-inflammatory, and notably whitening properties have already been largely documented [20,[37][38][39][40]. Apigenin, particularly promising for cancer prevention [41], also displays a variety of engaging activities and notably anti-inflammatory and anti-oxidant properties [39,42].…”
Section: Final Purification and Identification Of Active Compoundsmentioning
confidence: 99%
“…Advances in cleaner processing technologies, particularly in fermentation, molecular and genetic engineering, have increasingly allowed chemical industries to use plant-based, as opposed to petrochemical, feedstocks for the manufacture of commercially important chemicals (Xu et al, 2008). Green chemicals are not limited to the fuel sector but are also relevant to a range of commercial sectors, including the pharmaceutical, nutraceutical, cosmetic, food and beverage industries (Dong et al, 2011;Crozier et al, 2009;An et al, 2008;Aburjai and Natsheh, 2003). The world production of biomass each year is thought to exceed 1  10 14 Kg (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%